Physiological and transcriptomic responses in brown trout, Salmo trutta, to multiple stressors: Pesticide mixtures, elevated water temperature and the proliferative kidney disease - Anne-Sophie Voisin; Kristina Rehberger; Melanie Fasel; Rébecca Beauvais; Helmut Segner; Ingeborg Werner (Science of The Total Environment, 2025)

Physiological-dependent alterations on transcriptomic and proteomic patterns of the single and combined temperature and salinity-exposed hybrid grouper, Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ - Jun Bo; Ronghui Zheng; Yulu Jiang; Jincan Chen; Chao Fang; Christyn Bailey; Yusheng Zhang; Jae-Seong Lee; Helmut Segner (Aquaculture, 2023)

Editorial: Immunity and disease of aquatic organisms under the combined impact of anthropogenic stressors: mechanisms and disease outcomes - Anett Kristin Larsen; Elisabeth Holen; Helmut Segner (Frontiers in Marine Science, 2023)

Xenobiotic metabolism and its physiological consequences in high-Antarctic Notothenioid fishes - Anneli Strobel; Roger Lille-Langøy; Helmut Segner; Patricia Burkhardt-Holm; Anders Goksøyr; Odd André Karlsen (Polar Biology, 2022)
The Antarctic ecosystem is progressively exposed to anthropogenic contaminants, such as polycyclic aromatic hydrocarbons (PAHs). So far, it is largely unknown if PAHs leave a mark in the physiology of high-Antarctic fish. We approached this issue via two avenues: first, we examined the functional response of the aryl hydrocarbon receptor (Ahr), which is a molecular initiating event of many toxic effects of PAHs in biota. Chionodraco hamatus and Trematomus loennbergii served as representatives for high-Antarctic Notothenioids, and Atlantic cod, Gadus morhua as non-polar reference species. We sequenced and cloned the Ahr ligand binding domain (LBD) of the Notothenioids and deployed a GAL4-based luciferase reporter gene assay expressing the Ahr LBD. Benzo[ a ]pyrene (BaP), beta-naphthoflavone and chrysene were used as ligands for the reporter gene assay. Second, we investigated the energetic costs of Ahr activation in isolated liver cells of the Notothenioids during acute, non-cytotoxic BaP exposure. In the reporter assay, the Ahr LBD of Atlantic cod and the Antarctic Notothenioids were activated by the ligands tested herein. In the in vitro assays with isolated liver cells of high-Antarctic Notothenioids, BaP exposure had no effect on overall respiration, but caused shifts in the respiration dedicated to protein synthesis. Thus, our study demonstrated that high-Antarctic fish possess a functional Ahr that can be ligand-activated in a concentration-dependent manner by environmental contaminants. This is associated with altered cost for cellular protein synthesis. Future studies have to show if the toxicant-induced activation of the Ahr pathway may lead to altered organism performance of Antarctic fish.

Zooplankton Feeding Induces Macroscopical Gonad Malformations in Whitefish (Coregonus ssp.) from Lake Thun, Switzerland - Daniel Bernet; Thomas Wahli; Christoph Küng; Helmut Segner (Fishes, 2020)
Alterations in gonad morphology are widespread in wild fish populations. Whitefish (Coregonus spp.) from Lake Thun, Switzerland, display a high prevalence of macroscopical gonad malformations including fusions to the musculature, segmented gonads and intersex condition. The aim of the present study was to evaluate whether the gonad morphological changes in Lake Thun whitefish are caused by genetic factors, environmental factors (water, diet) or “gene × environment” interaction. We performed two independent experiments of a three-year duration in which we reared whitefish from fertilization until adulthood and tested the possible causative factors using a matrix design: (i) genetics—comparing the prevalence of gonad malformations in whitefish of different genetic origin reared under identical environmental conditions (same diet, same water, same experimental facility); (ii) environment—comparing the prevalence of gonad malformations in whitefish of the same genetic origin reared in different water sources and/or fed with different diets; and (iii) gene-environment interaction—comparing the prevalence of gonad morphological alterations in relation to the combinations of genetics and environmental factors. Two diets were used for the rearing experiments: either zooplankton collected in Lake Thun which represents the natural diet of whitefish, or an artificial dry food which was used as control. The key finding of this study is that the inducing factor of the gonad malformations is contained in the zooplankton of Lake Thun. Fish fed with this diet developed a significantly higher prevalence of malformations than fish from any other treatment, irrespective of the genetic origin and/or the water source. This result could be repeated in the two independent experiments. Importantly, the prevalence values observed in the experimental fish fed with Lake Thun zooplankton were similar to the prevalence values recorded in free-ranging whitefish in the lake. The findings of this study advance the understanding of the causes of gonad morphological alterations in wild fish populations.

Trade-Offs Underwater: Physiological Plasticity of Rainbow Trout (Oncorhynchus mykiss) Confronted by Multiple Stressors - Elena Wernicke von Siebenthal; Kristina Rehberger; Christyn Bailey; Albert Ros; Elio Herzog; Helmut Segner (Fishes, 2018)
Organisms have evolved mechanisms to partition the available resources between fitness-relevant physiological functions. Organisms possess phenotypic plasticity to acclimate to changing environmental conditions. However, this comes at a cost that can cause negative correlations or “trade-offs”, whereby increasing investments in one function lead to decreased investments in another function. The aim of the present study was to investigate the prioritization of resource allocation between growth, pathogen defense, and contaminant response in juvenile rainbow trout (Oncorhynchus mykiss) exposed to changes of resource income or expenditure. We performed a multifactorial experiment with three resource-impacting stressors—limited food availability, a parasitic infection, exposure to a vitellogenesis-inducing contaminant—and combinations thereof. Treatment with the individual stressors evoked the expected responses in the respective physiological target systems—body growth, immune system, and hepatic vitellogenin transcription—but we found little evidence for significant negative relations (trade-offs) between the three systems. This also applied to fish exposed to combinations of the stressors. This high phenotypic flexibility of trout in their resource allocation suggests that linear resource allocations as mechanisms of phenotypic plasticity may be too simplistic, but it also may point to a greater capacity of ectothermic than endothermic vertebrates to maintain key physiological processes under competing resource needs due to lower maintenance costs.

The emergence of epitheliocystis in the upper Rhone region: evidence for Chlamydiae in wild and farmed salmonid populations - Maricruz Guevara Soto; Beatriz Vidondo; Lloyd Vaughan; Helena M. B. Seth-Smith; Lisbeth Nufer; Helmut Segner; Jean-Francois Rubin; Heike Schmidt-Posthaus (Archives of Microbiology, 2016)

Molecular and cellular effects of contamination in aquatic ecosystems - Miriam Hampel; Julian Blasco; Helmut Segner (Environmental Science and Pollution Research, 2015)

Morphological alterations in the liver of yellow perch (Perca flavescens) from a biological mercury hotspot - Anne-Katrin Müller; Markus Brinkmann; Lisa Baumann; Michael H. Stoffel; Helmut Segner; Karen A. Kidd; Henner Hollert (Environmental Science and Pollution Research, 2015)

Prochloraz causes irreversible masculinization of zebrafish (Danio rerio) - Lisa Baumann; Susanne Knörr; Susanne Keiter; Tina Nagel; Helmut Segner; Thomas Braunbeck (Environmental Science and Pollution Research, 2015)

Estrogen Modulates Hepatic Gene Expression and Survival of Rainbow Trout Infected with Pathogenic Bacteria Yersinia ruckeri - Michael Wenger; Aleksei Krasnov; Stanko Skugor; Elinor Goldschmidt-Clermont; Ursula Sattler; Sergey Afanasyev; Helmut Segner (Marine Biotechnology, 2012)

Immunotoxic effects of environmental toxicants in fish — how to assess them? - Helmut Segner; Michael Wenger; Anja Maria Möller; Bernd Köllner; Ayako Casanova-Nakayama (Environmental Science and Pollution Research, 2012)

Gender-specific modulation of immune system complement gene expression in marine medaka Oryzias melastigma following dietary exposure of BDE-47 - Roy R. Ye; Elva N. Y. Lei; Michael H. W. Lam; Alice K. Y. Chan; Jun Bo; Jason P. van de Merwe; Amy C. C. Fong; Michael M. S. Yang; J. S. Lee; Helmut E. Segner; Chris K. C. Wong; Rudolf S. S. Wu; et al. (Environmental Science and Pollution Research, 2012)

A natural freshwater origin for two chlamydial species, Candidatus Piscichlamydia salmonis and Candidatus Clavochlamydia salmonicola, causing mixed infections in wild brown trout ( Salmo trutta ) - Heike Schmidt‐Posthaus; Adam Polkinghorne; Lisbeth Nufer; Andrea Schifferli; Dieter R. Zimmermann; Helmut Segner; Pascale Steiner; Lloyd Vaughan (Environmental Microbiology, 2012)
Summary Gill disease in salmonids is characterized by a multifactorial aetiology. Epitheliocystis of the gill lamellae caused by obligate intracellular bacteria of the order Chlamydiales is one known factor; however, their diversity has greatly complicated analyses to establish a causal relationship. In addition, tracing infections to a potential environmental source is currently impossible. In this study, we address these questions by investigating a wild brown trout ( Salmo trutta ) population from seven different sites within a Swiss river system. One age class of fish was followed over 18 months. Epitheliocystis occurred in a site‐specific pattern, associated with peak water temperatures during summer months. No evidence of a persistent infection was found within the brown trout population, implying an as yet unknown environmental source. For the first time, we detected ‘ Candidatus Piscichlamydia salmonis’ and ‘ Candidatus Clavochlamydia salmonicola’ infections in the same salmonid population, including dual infections within the same fish. These organisms are strongly implicated in gill disease of caged Atlantic salmon in Norway and Ireland. The absence of aquaculture production within this river system and the distance from the sea, suggests a freshwater origin for both these bacteria and offers new possibilities to explore their ecology free from aquaculture influences.

Health of farmed fish: its relation to fish welfare and its utility as welfare indicator - Helmut Segner; Henrik Sundh; Kurt Buchmann; Jessica Douxfils; Kristina Snuttan Sundell; Cédric Mathieu; Neil Ruane; Fredrik Jutfelt; Hilde Toften; Lloyd Vaughan (Fish Physiology and Biochemistry, 2012)

Global proteomics analysis of testis and ovary in adult zebrafish (Danio rerio) - Ksenia J. Groh; Victor J. Nesatyy; Helmut Segner; Rik I. L. Eggen; Marc J.-F. Suter (Fish Physiology and Biochemistry, 2011)

Assessment of fish health status in four Swiss rivers showing a decline of brown trout catches - Simone Zimmerli; Daniel Bernet; Patricia Burkhardt-Holm; Heike Schmidt-Posthaus; Pascal Vonlanthen; Thomas Wahli; Helmut Segner (Aquatic Sciences, 2007)

Monitoring Pollution in River MureŞ, Romania, Part III: biochemical effect markers in fish and integrative reflection - Heinz-R. Köhler; Cristina Sandu; Volker Scheil; Erika M. Nagy-Petrică; Helmut Segner; Ilie Telcean; Gheorghe Stan; Rita Triebskorn (Environmental Monitoring and Assessment, 2007)

15N Metabolic test for the determination of phytotoxic effects of chemicals and contaminated environmental samples - Klaus Jung; Karin Kaletta; Helmut Segner; Gerrit Schüürmann (Environmental Science and Pollution Research, 1999)

Antiestrogenic activity of anthropogenic and natural chemicals - José María Navas; Helmut Segner (Environmental Science and Pollution Research, 1998)

Spontaneous formation of intercellular bile canaliculi and hybrid biliary-pancreatic canaliculi in co-culture of hepatocytes and exocrine pancreas cells from carp - Gnter Vogt; Helmut Segner (Cell and Tissue Research, 1997)